Johannes Dreyer (1500–1544) – Die Hervormer van Herford - Dreyer, Wim (HTS teologiese studies, 2017)
During 2017, churches with roots in the 16th century Reformation look back at five centuries of reformed Christianity. Much attention is given to important leaders of the Reformation such as Luther and Calvin. However, there are many forgotten ‘heroes’ who will receive no accolades, nor will they be mentioned in any publication. In this contribution the author tells the story of dr Johannes Dreyer, the forgotten reformer of Herford in Westphalia (Germany). After giving some biographical and contextual information, Dreyer’s church order, which was published in 1534 in Wittenberg, is discussed in terms of language, structure and theological content. The conclusion is reached that the implementation of new church orders were an integral part of the reformation process as well as applying reformed doctrine to the practical situation of churches.